Examining the Triad of Personality, Cognition, and Quality of Life in Alcohol and Opioid Consumers - Arora, Rosy; Srivastava, Kiran (Journal of Neonatal Surgery, 2025)
Substance use disorders (SUDs), especially opioid and alcohol dependence, are significant challenges to public health, affecting personal characteristics, cognitive functions and quality of life (QoL). This paper examined these dimensions in young adults and seeks to compare the results between opioid and alcohol users. A cross-sectional research design was used, and participants were purposively selected from de-addiction clinics in Punjab, India; 50 opioid and 50 alcohol users were selected. Self-administered questionnaires and quantitative tests such as descriptive analysis and independent sample t-tests were used to assess personality traits, QoL, and cognitive functioning with the help of SPSS. Outcomes show that alcohol consumers get higher scores on personality tests and have more consistent traits than opioid consumers. However, no differences were observed in QoL between the two groups, and both groups experienced considerable physical, psychological and social difficulties. Analysis revealed that opioid users performed slightly better on cognitive tests, but the variability for cognitive functioning was higher in opioid users. The present findings indicate that alcohol and opioid dependence differently affect the psychological and cognitive characteristics of the patients. The results enhance the knowledge of how personality characteristics affect cognitive and QoL outcomes and facilitate the treatment and rehabilitation process of SUD clients